If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -9x = 60 + -23x Solving 6 + -9x = 60 + -23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23x' to each side of the equation. 6 + -9x + 23x = 60 + -23x + 23x Combine like terms: -9x + 23x = 14x 6 + 14x = 60 + -23x + 23x Combine like terms: -23x + 23x = 0 6 + 14x = 60 + 0 6 + 14x = 60 Add '-6' to each side of the equation. 6 + -6 + 14x = 60 + -6 Combine like terms: 6 + -6 = 0 0 + 14x = 60 + -6 14x = 60 + -6 Combine like terms: 60 + -6 = 54 14x = 54 Divide each side by '14'. x = 3.857142857 Simplifying x = 3.857142857
| x^2+x-(-2x)=x^2+12 | | -1/8*9 | | 25*7*6+8+8-79= | | 61-2x=7x+19 | | 5/6x=-20 | | 6-9x=126-37x | | 6-1x8+12/4 | | 3m+7=35 | | 8/5x=32 | | 5a+2=3a | | 3-18u=-4u-12 | | 5+45/9-6 | | -13x=-65 | | 2(4+3m)=7(m+2) | | (n-5)*8=40 | | n+44-29n= | | x-28=119 | | a-3.1=6.6-4a | | 20-35u=-u-48 | | 2(3x-1)=-6(3+9x) | | 4x+6x=55-3x | | 23p-13p= | | -4n-6m=15+m | | 2z+14=9z | | 1/5x=2 | | B-5.3=20 | | 2(4+3x)=7(x+2) | | -12x+17=-89 | | A-30=-23 | | -4(8-3x)=2x+8 | | 4/n=n/16 | | 1/4s=-1 |